Synthesis and Antimicrobial Activity of 1-Furyl-3- (substituted phenyl)-2-propene-1-one - Bhendkar, A.H.; Doshi, A.G.; Raut, A.W. (Asian Journal of Chemistry, 2010)
2-Acetyl furan was condensed with different aromatic aldehyde in ethanol medium in presence of aqueous alkali and the thick mass was decomposed by dilute hydrochloric acid to get 1-furyl-3-(substituted phenyl)- 2-propene-1-one. The structure elucidation of these compounds were done on the basis of chemical and spectral data. The antibacterial activity of these compounds have also been screened and found to be effective against both gram positive and gram negative bacteria.